SOCIAL TRANSFORMATIONS IN A MIDDLE PRECLASSIC COMMUNITY: ELITE RESIDENTIAL COMPLEXES AT CEIBAL. Issue 1 (31st May 2017) - Triadan, Daniela; Castillo, Victor; Inomata, Takeshi; Palomo, Juan Manuel; Méndez, María Belén; Cortave, Mónica; MacLellan, Jessica; Burham, Melissa; Ponciano, Erick
Abstract: Excavations in large platforms in the center of Ceibal revealed extensive early Middle Preclassic constructions. They consisted of extensive clay platforms that supported low basal structural platforms. Although the function of the earliest platform, Sulul, during the Real-Xe 1 and 2 phases (950–775b.c. ) is not clear, the one built during the Real-Xe 3 phase (775–700b.c. ) likely supported multiple residential buildings. The emphasis on elevating this domestic space above the natural land surface and the communal labor involved in these constructions indicate that they were most likely inhabited by an emergent elite. These places were continuously remodeled and used until the end of the Middle Preclassic. This new data from Ceibal contributes significantly to our understanding of the processes involved in the transition to a sedentary lifestyle and the development of social and political differentiation in the Maya lowlands.